Ultralow-thermal-conductivity self-rebound heat-preservation and heat-insulation protective paint and protective coating
The existing coatings are solved in plateau areas by using modified polymer expansion microspheres, modified mineral fibers and PVA toughened modified hydrophobic silica aerogels in the aerogel insulation and thermal protection coating. In the application, poor toughness and easy cracking have been achieved, and the coating with ultra-low thermal conductivity and self-resistance effect has been significantly improved.
Patent Information
- Application Number
- CN202311016731.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-11
- Publication Date
- 2025-02-18
AI Technical Summary
In the application of existing aerogel insulation and thermal protection coatings in plateau areas, there are problems such as poor toughness, easy cracking, low strength, insufficient adhesion to the substrate and high thermal conductivity, which is difficult to meet the temperature in plateau areas. Wet regulation' demand.
Using an ultra-low thermal conductivity self-resistance insulation and thermal insulation protective coating, including silicone emulsion, modified polymer expansion microspheres, modified mineral fibers and PVA toughened modified hydrophobic silica aerogels, etc., through The silane coupling agent modification treatment enhances the surface-active groups of polymer expanded microspheres and mineral fibers, forming stable chemical bonds to improve the curing crosslinking and mechanical strength of the coating.
It achieves ultra-low thermal conductivity, self-resistance effect of the coating, improves the toughness and mechanical strength of the coating, enhances the adhesion to the substrate, significantly reduces the thermal conductivity, and improves the thermal insulation performance.
Smart Images

Figure CN119463589A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of thermal insulation protective coatings, and in particular to an ultra-low thermal conductivity self-resilient thermal insulation protective coating and a protective coating. Background Art
[0002] In Xinjiang, Tibet, central and western regions and other plateau areas, the environment is generally harsh, the terrain is complex and the average altitude is high. It is extremely challenging to build strategic trunk channels in these places. Under normal circumstances, the temperature decreases with the increase of altitude. The temperature drops by about 0.6℃ for every 100m increase in altitude, which makes the average temperature in these areas low all year round. In addition, these plateau areas have sufficient sunshine during the day and strong solar radiation intensity, which makes the surrounding temperature rise rapidly, the water evaporation rate increases, and the relative humidity of the environment decreases, while the temperature drops sharply at night. Usually, positive and negative temperatures often alternate in a day. Under this service condition, the slump loss of concrete structures increases, shrinkage cracking intensifies, and cement hydration is affected. At the same time, high-frequency positive and negative temperature alternation accelerates the freeze-thaw damage of concrete, making it difficult to ensure its strength and durability, affecting the service life of the building. The existing conventional aerogel thermal insulation and heat protection coatings generally have high thermal conductivity, small insulation temperature difference, poor adhesion to concrete substrates or primers, and are very easy to crack and peel off under strong winds, dryness and large temperature differences. It is difficult to meet the thermal insulation and protection needs of the plateau "temperature and humidity control".
[0003] In order to solve the problem of cracking during coating curing and further improve the thermal insulation performance of the coating, researchers added various polymers, toughened fibers and hollow microspheres to the coating.
[0004] Patent CN 115197619 A discloses the preparation of a new type of environmentally friendly aerogel thermal insulation coating, which adds thermal insulation fillers such as glass beads and aerogel to an aqueous acrylic resin solution and oscillates it at high speed, which will cause some of the glass beads to shatter and affect the thermal insulation effect; in addition, the aerogel without any modification will also have the above problems, causing the coating to solidify and crack and affect the thermal insulation effect.
[0005] Patent CN 115418122 A discloses a method for preparing a water-based aerogel thermal insulation coating. The coating includes silica sol, polyvinyl alcohol, aerogel powder, hollow glass microspheres, silicon carbide, silicon dioxide, titanium dioxide, dispersant, defoamer, ammonia solution, alumina fiber and aluminum silicate fiber. Polyvinyl alcohol can effectively improve the defects of cracks and micropores that are easy to generate when silica sol is formed into a film alone; filling powder is added to fully ensure the existence of nano-scale porous structure in aerogel; alumina fiber and aluminum silicate fiber as reinforcing materials can significantly and effectively improve the thermal insulation performance and toughness of the coating. However, the hollow glass microspheres are crushed during the preparation process, and it is difficult to introduce more pores when used in the coating, so it does not have any thermal insulation effect. On the contrary, the higher thermal conductivity of the glass fragments will improve the thermal conductivity of the coating.
[0006] Patent CN 115109471 A discloses a modified silica aerogel thermal insulation coating and its preparation method. The modified silica aerogel prepared by this scheme is easy to disperse in the coating and is not easy to agglomerate, so it has a better thermal insulation effect. However, it should not be ignored that the minimum mass percentage of the modified silica aerogel is greater than 13%. During the curing process of the coating, the modified silica aerogel can easily collapse and break due to external forces, which significantly reduces the porosity and pore size, thus affecting the thermal insulation effect of the coating and its own mechanical strength. Secondly, the added auxiliary filler and the film-forming material are only simply physically combined, which makes it very easy for microcracks to appear during the curing process of the coating, and the strength of the coating itself will also be greatly reduced. In addition, the outer shell of the auxiliary filler ceramic hollow microspheres has poor toughness and is brittle, which is easily broken at a stirring rate of 500-800r / min, reducing its thermal insulation effect in the coating.
[0007] In addition, the film-forming substances used in the above patents are basically one or more of acrylic resin emulsions, potassium / sodium / lithium silicate, and silica sol. The crosslinking degree and density of the cured network of these film-forming substances are relatively low, so their thermal insulation, flexibility and corrosion resistance are poor. Summary of the invention
[0008] In view of the defects of existing aerogel thermal insulation protective coatings such as poor toughness and easy cracking, low self-strength, low adhesion to the substrate surface, and high thermal conductivity, the present invention provides an ultra-low thermal conductivity self-resilient thermal insulation protective coating and protective coating, which not only solves the problems existing in the prior art, but also has a simple preparation process, mild synthesis conditions, and low equipment requirements. It is a thermal insulation protective coating with excellent comprehensive performance.
[0009] The invention discloses an ultra-low thermal conductivity self-resilient thermal insulation protective coating, which comprises, by weight, 10-15 parts of silicone resin emulsion, 15-25 parts of acrylic resin emulsion, 15-20 parts of modified polymer expanded microspheres, 10-15 parts of modified mineral fibers, 5-8 parts of polyvinyl alcohol (PVA) toughened modified hydrophobic silica (SiO2) aerogel, 1-5 parts of a crosslinking agent, 0.1-1 parts of a catalyst, 0.1-0.5 parts of a thickener, 3-5 parts of a dispersant, 1-2 parts of a defoaming agent, 5-8 parts of a film-forming aid, 0.1-0.5 parts of a pH adjuster, 1.5-2 parts of ethylene glycol, and 10-15 parts of deionized water.
[0010] The modified polymer expanded microspheres are polymer expanded microspheres surface-modified with silane coupling agent I, the polymer expanded microspheres are thermoplastic acrylate polymer / thermoplastic acrylonitrile copolymer shells coated with alkane or alkyne gas after heating and expansion, and the particle size of the polymer expanded microspheres ranges from 20 to 60 μm; the polymer expanded microspheres are selected from Expancel 044WE 20 ( Solid content 15%), Expancel 921WE 40 ( Solid content 10%), MH-30W15 ( Solid content 15%), MH-60W15 ( The above-mentioned silane coupling agent I is selected from γ-mercaptopropyltrimethoxysilane (KH-591), chloro(dimethylaminoethyl methacrylate)propyltrimethoxysilane (Cl - CH2=CMeCOOC2H4Me2N + C3H6Si(OMe)3), 4-[2-(trimethoxysilyl)ethyl]benzene-1-sulfonyl azide (N3SO2C6H4CH2CH2Si(OMe)3); the concentration of the silane coupling agent I is 1-2wt.%; the mass volume ratio of the polymer expanded microspheres to the silane coupling agent is (1-5)g:100ml. If the volume content of the silane coupling agent is low, the polymer expanded microspheres will be difficult to be loaded and the modification effect will not be obvious, the surface active group content will be low, the chemical crosslinking effect formed by the silicone resin emulsion and the crosslinking agent in the actual application of the coating will be weak, and the final coating curing will make it easier for microcracks to appear between the two; if the volume content of the silane coupling agent is high, it will cause a certain degree of waste, and more silane coupling agent will not have a better modification effect.
[0011] Preferably, the silane coupling agent I is γ-mercaptopropyltrimethoxysilane (KH-591).
[0012] The preparation method of silane coupling agent I modified polymer expanded microspheres comprises the following steps: 1) preparing a silane coupling agent dilute solution with a concentration of 1-2wt.%, and except for the aminohydrocarbon silane coupling agent, the dilute solution prepared by other silane coupling agents needs to add acetic acid to adjust the pH of the solution to between 3.5 and 5.5; 2) adding a certain mass of polymer expanded microspheres to the silane coupling agent dilute solution in step 1) and mechanically stirring at room temperature for 30-60 minutes, taking out and immersing in deionized water for rinsing 2-3 times, drying and transferring to a 50-60°C oven for drying for 2-3 hours, and drying at room temperature for 24 hours, so as to obtain modified polymer expanded microspheres with active reactive groups on the surface.
[0013] The solvent used to prepare the dilute solution of silane coupling agent I with a concentration of 1-2 wt.% is water, ethanol, isopropanol or a water-alcohol mixture.
[0014] The polymer expanded microspheres of the present invention are gaseous alkanes / alkynes @ thermoplastic polymers, and their shells are tough and elastic, which makes the prepared coatings have excellent self-rebounding effects. In addition, the microspheres have higher mechanical strength than the hollow glass / ceramic microspheres in traditional thermal insulation coatings, and the traditional dispersion disk or stirring paddle can be used for mechanical stirring and dispersion during the coating preparation process without the microspheres being broken. Secondly, the chemical mineral composition and crystal structure of the thermoplastic polymer shell are more complex than those of traditional inorganic glass, ceramics, etc., so the thermal conductivity is lower; in addition, the alkane / alkyne gas encapsulated inside the microspheres has a larger molecular weight than air and a relatively complex structure, so the thermal conductivity is also lower.
[0015] The modified mineral fiber is a mineral fiber surface-modified by a silane coupling agent II; the mineral fiber is a composite of any one or more of sepiolite fiber, aluminum silicate fiber, and brucite fiber, and the particle size of the mineral fiber is 1-3 mm; the silane coupling agent II is selected from vinyl trimethoxy silane (KH-171), vinyl triethoxy silane (SCA-1603), vinyl triacetoxy silane (KH-188), vinyl-tri(2-methoxyethoxy) silane (SCA-1623), γ-aminopropyl triethoxy silane (KH-550), 3-(phenylamino)propyl trimethoxy silane (XH-118), N-β-(aminoethyl)-γ-amino Propyltrimethoxysilane (KH-792), 3-[2-(2-aminoethylamino)ethylamino]propyltrimethoxysilane (KH-892), 3-chloropropyltrimethoxysilane (KH-431), 3-(methacryloyloxy)propyltrimethoxysilane (KH-570), γ-mercaptopropyltrimethoxysilane (KH-591), γ-mercaptopropyltriethoxysilane (KH-580), γ-aminopropylmethyldiethoxysilane (KH-902) are compounded in any one or more thereof; the concentration of the above-mentioned silane coupling agent II is 1-2wt.%; the mass volume ratio of the above-mentioned mineral fiber to the silane coupling agent is preferably (0.5-2)g:100ml.
[0016] Preferably, the silane coupling agent II is γ-aminopropyltriethoxysilane (KH-550).
[0017] The preparation method of silane coupling agent modified mineral fiber comprises the following steps: 1) preparing a 1-2wt.% concentration of silane coupling agent dilute solution, except for amino-hydrocarbon silane coupling agent, acetic acid is added to the dilute solution prepared by other silane coupling agents to adjust the pH of the solution to between 3.5 and 5.5; 2) adding a certain mass of mineral fiber to the silane coupling agent dilute solution in step 1) for ultrasonic dispersion for 1-2 hours, taking out and immersing in deionized water for rinsing and filtering 2-3 times, drying and moving into a 50-60°C oven for drying for 2-3 hours, drying at room temperature for 24 hours, grinding and sieving, and obtaining modified mineral fiber with active reactive groups on the surface.
[0018] The solvent used to prepare the 1-2 wt.% concentration of the silane coupling agent II dilute solution is water, ethanol, isopropanol or a water-alcohol mixture.
[0019] On the one hand, mineral fiber, as a thermal insulation filler, has excellent thermal insulation effect and can effectively reduce the thermal conductivity of the protective coating; secondly, mineral fiber has high chemical and mechanical stability, which can further improve the toughness and mechanical strength of the thermal insulation protective coating, avoiding the problem of cracking and peeling that is easy to occur after drying like traditional thermal insulation protective coatings. On the other hand, mineral fiber can construct a maze effect in the thermal insulation protective coating, making it have good water resistance and corrosion resistance.
[0020] The above-mentioned polyvinyl alcohol toughened and modified hydrophobic silica aerogel, the average molecular weight of the above-mentioned polyvinyl alcohol is 70000-85000, the viscosity is 20-32mPa·s, the concentration is 1-3wt.%, and the above-mentioned polyvinyl alcohol is selected from any one or more of the commercially available 1788, 1792, 1795, 1796, 1797, and 1798; the mass ratio of the above-mentioned polyvinyl alcohol to the hydrophobic silica aerogel is preferably 10: (0.8-1.2).
[0021] Preferably, the polyvinyl alcohol is selected from commercially available 1788.
[0022] The preparation method of PVA toughened modified hydrophobic SiO2 aerogel comprises the following steps: 1) placing a certain mass of PVA solid powder in deionized water at 60°C and stirring and dissolving it to prepare a PVA aqueous solution with a concentration of 1-3wt.%; 2) adding a certain mass of hydrophobic aerogel powder to the PVA aqueous solution in step 1) and mechanically stirring it at a speed of 300-500rpm and 60°C for 36-48h, taking it out and transferring it to a freeze dryer for drying for 36-48h, and then crushing and sieving to obtain a toughened modified hydrophobic SiO2 aerogel supported by a PVA skeleton network.
[0023] The silicone resin emulsion is a hydroxyl-terminated polymethylphenylsiloxane emulsion, and its organic solvent and emulsifier content is less than 10%, and the solid content is not less than 50%, which can better adjust the formula and reduce the water content in the system. The coating produced in this way is in better condition and is not easy to crack. The overall resin emulsion in the system contains a relatively large amount of film-forming substances, so that the final coating has higher strength and greater bonding strength. The acrylic resin emulsion is selected from any one or more of pure acrylic emulsion, styrene acrylic emulsion, silicone acrylic emulsion, and vinegar acrylic emulsion, and the solid content of the acrylic resin emulsion is 45%-55%.
[0024] The crosslinking agent is any one of polyol esters, polyalkoxysilanes, and organic ketoxime silanes.
[0025] The catalyst is a combination of any one or more of tin cyclohexaneate, dibutyltin dilaurate, stannous octoate and hexachlorocyclotriphosphazene.
[0026] The thickener is selected from any one of hydroxyethyl cellulose and polyurethane associative thickener; preferably, the hydroxyethyl cellulose is 250HHBR, 250HBR, and the polyurethane associative thickener is RM-8W, TEGO Viscoplus 3030, and RHEOBYK-H 6500VF.
[0027] The dispersant is selected from any one or more of polycarboxylate ammonium salt dispersants, alkylhydroxyl ammonium salt dispersants, and non-ionic modified fatty acid derivative dispersants; the polycarboxylate ammonium salt dispersants are SN-5027 and SN-5029, the alkylhydroxyl ammonium salt dispersants are BYK-180 and BYK-181, and the non-ionic modified fatty acid derivative dispersant is TEGO Dispers740W.
[0028] The defoamer is selected from any one or more of polyether siloxane defoamers, polysiloxane defoamers, metal soap defoamers, and paraffin defoamers; the polyether siloxane defoamers are TEGO Airex 901W and TEGO Airex 902W, the polysiloxane defoamers are BYK-022 and BYK-023, the metal soap defoamers are NOPCO NXZ and SN-1390, and the paraffin defoamers are SN-1340 and SN-1360.
[0029] The film-forming aid is selected from any one or more of alcohol ester dodeca, propylene glycol butyl ether, and dipropylene glycol butyl ether; alcohol ester dodeca is preferred.
[0030] The pH adjuster is 2-amino-2-methyl-1-propanol.
[0031] A method for preparing an ultra-low thermal conductivity self-resilient thermal insulation protective coating comprises the following steps: (1) placing deionized water, a thickener, a pH regulator, a dispersant, a defoaming agent, modified mineral fibers and polyvinyl alcohol toughened modified hydrophobic silica aerogel in a container, and dispersing and mixing them uniformly at a speed of 800-1000 rpm at room temperature, then reducing the speed to 400-500 rpm, adding silicone resin emulsion, acrylic resin emulsion, ethylene glycol, a film-forming aid, modified polymer expanded microspheres, a cross-linking agent, a catalyst and part of the deionized water in sequence, and continuing mechanical stirring for 30 minutes, thereby obtaining an ultra-low thermal conductivity self-resilient thermal insulation protective coating.
[0032] A protective coating is formed by curing the ultra-low thermal conductivity self-resilient thermal insulation protective coating. The ultra-low thermal conductivity self-resilient thermal insulation protective coating is scraped on the surface of the substrate after surface treatment, and the thickness of the coating can be scraped at one time to a thickness of 0.5-5 mm, and then cured and dried under standard conditions to obtain an ultra-low thermal conductivity self-resilient thermal insulation protective coating.
[0033] Compared with the prior art, the present invention has the following advantages:
[0034] 1) The surfaces of polymer expanded microspheres modified by silane coupling agent I and mineral fibers modified by silane coupling agent II contain active groups that can form stable chemical bonds with silicone resin emulsions and crosslinking agents, thereby effectively improving the curing and crosslinking degree of the thermal insulation protective coating itself, making the solid phase crystal structure more complex, thereby further reducing thermal conductivity and improving coating strength. On the other hand, the interfacial bonding strength between polymer expanded microspheres, mineral fibers and film-forming substances is further improved.
[0035] 2) PVA toughened and modified hydrophobic SiO2 aerogel, which uses polyvinyl alcohol to construct a skeleton network to support the hydrophobic aerogel, improves the defects of poor toughness and easy collapse of the hydrophobic aerogel itself, solves the problem of dispersion and agglomeration of hydrophobic aerogel in the coating, and enables the aerogel to better play the role of thermal insulation. At the same time, it avoids the problem of cracking and collapse of the thermal insulation protective coating when it is dry.
[0036] 3) Hydroxyl-terminated polymethylphenylsiloxane emulsion, due to the influence of phenyl electronic effect and steric effect, shows better high and low temperature resistance, damping performance and compatibility with acrylic resin emulsion compared with traditional hydroxyl-terminated polydimethylsiloxane. In addition, the solidified interpenetrating network cross-linking effect between silicone resin emulsion and cross-linking agent, silane coupling agent and acrylic resin emulsion improves the solid phase crystallinity of the coating, making the coating more dense, which has better thermal insulation, flexibility and corrosion resistance than single acrylic resin emulsion film-forming materials. On the other hand, the presence of phenyl further improves the bonding strength and self-strength between the thermal insulation protective coating and the concrete substrate or primer.
[0037] 4) The protective coating obtained by curing the ultra-low thermal conductivity self-resilient thermal insulation protective coating of the present application has a thermal conductivity coefficient of up to 0.0180W / (m·k) at 25°C. When the thickness is 1mm, the maximum insulation temperature difference compared with the blank test plate after heating at 80°C with a non-contact infrared lamp for 15 minutes can reach more than 35°C; the maximum insulation temperature difference compared with the blank test plate after heating at 80°C with a contact heating platform for 15 minutes can reach more than 40°C, and the upper surface temperature change is only within 1.5°C.
[0038] The preparation process of the ultra-low thermal conductivity self-resilient thermal insulation protective coating provided in this application is simple, the modification conditions of key raw materials are mild, and the requirements for instruments and equipment are low. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 The coating rebound test effect diagram obtained in Example 8 and Comparative Example 11; DETAILED DESCRIPTION
[0040] The technical scheme of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. In this application, unless otherwise specified, all percentage contents are mass percentages.
[0041] The polyvinyl alcohol used in each embodiment and comparative example is selected from commercially available 1788.
[0042] Example 1
[0043] 1) Preparation of modified polymer expanded microspheres, modified mineral fibers and PVA toughened modified hydrophobic SiO2 aerogel:
[0044] Take 100g Expancel 044WE 20( Solid content 15% polymer expanded microspheres (pure microsphere mass 15g) were added into 1000ml of 2wt.% KH-591 dilute solution and mechanically stirred for 40min, then taken out, rinsed and dried to obtain the modified polymer expanded microspheres.
[0045] 12 g of sepiolite mineral fiber was added into 800 ml of 1.5 wt.% KH-550 dilute solution and ultrasonically dispersed for 2 h. The solution was taken out, rinsed, dried, ground and sieved to obtain the modified mineral fiber.
[0046] 8 g of hydrophobic SiO2 aerogel was added into 100 ml of 2 wt.% PVA dilute solution and mechanically stirred for 48 h. The solution was taken out, freeze-dried, crushed and sieved to obtain the PVA toughened and modified hydrophobic SiO2 aerogel.
[0047] 2) Preparation of thermal insulation protective coating:
[0048] 15 parts by mass of deionized water, 0.35 parts by mass of thickener, 0.4 parts by mass of pH adjuster, 5 parts by mass of dispersant, 2 parts by mass of defoamer, 12 parts by mass of modified mineral fiber and 8 parts by mass of PVA toughened modified hydrophobic SiO2 aerogel are placed in a container and dispersed and mixed evenly at high speed. Then the speed is reduced and 13 parts by mass of silicone resin emulsion, 22 parts by mass of styrene acrylic emulsion, 1.5 parts by mass of ethylene glycol, 8 parts by mass of film-forming aid, 15 parts by mass of modified polymer expanded microspheres, 4 parts by mass of cross-linking agent polyethylene adipate and 0.1 parts by mass of catalyst dibutyltin dilaurate are added in sequence and mechanical stirring is continued for 30 minutes to obtain a mixed coating.
[0049] The mixed coating was then scraped onto the surface of the surface treated concrete substrate with a thickness of 1 mm and cured and dried under standard conditions to obtain a self-resilient thermal insulation protective coating with ultra-low thermal conductivity.
[0050] Example 2
[0051] 1) Preparation of modified polymer expanded microspheres, modified mineral fibers and PVA toughened modified hydrophobic SiO2 aerogel:
[0052] Take 120g MH-30W15( Solid content 15% polymer expanded microspheres (pure microsphere mass 18g) were added into 600ml of 1.8wt.% dilute solution of (dimethylaminoethyl methacrylate)propyltrimethoxysilane chloride and mechanically stirred for 50min, then taken out, rinsed and dried to obtain the modified polymer expanded microspheres.
[0053] 10 g of aluminum silicate mineral fiber was added into 800 ml of 2 wt.% KH-188 dilute solution and ultrasonically dispersed for 1.5 h. The fiber was taken out, rinsed, dried, ground and sieved to obtain the modified mineral fiber.
[0054] 5 g of hydrophobic SiO2 aerogel was added into 50 ml of 2.5 wt.% PVA dilute solution and mechanically stirred for 40 h. The solution was taken out, freeze-dried, crushed and sieved to obtain the PVA toughened and modified hydrophobic SiO2 aerogel.
[0055] 2) Preparation of thermal insulation protective coating:
[0056] 12 parts by mass of deionized water, 0.4 parts by mass of thickener, 0.3 parts by mass of pH adjuster, 3 parts by mass of dispersant, 1.5 parts by mass of defoamer, 10 parts by mass of modified mineral fiber and 5 parts by mass of PVA toughened modified hydrophobic SiO2 aerogel are placed in a container and dispersed and mixed evenly at high speed. Then the speed is reduced and 12.5 parts by mass of silicone resin emulsion, 25 parts by mass of silicone acrylic emulsion, 2 parts by mass of ethylene glycol, 7 parts by mass of film-forming aid, 18 parts by mass of modified polymer expanded microspheres, 2 parts by mass of cross-linking agent methyl tributylidene silane and 0.5 parts by mass of catalyst stannous octoate are added in sequence and mechanical stirring is continued for 30 minutes to obtain a mixed coating.
[0057] The mixed coating was then scraped onto the surface of the surface treated concrete substrate with a thickness of 1 mm and cured and dried under standard conditions to obtain a self-resilient thermal insulation protective coating with ultra-low thermal conductivity.
[0058] Example 3
[0059] 1) Preparation of modified polymer expanded microspheres, modified mineral fibers and PVA toughened modified hydrophobic SiO2 aerogel:
[0060] Take 106.67g MH-60W15( Solid content 15% polymer expanded microspheres (pure microsphere mass 16g) were added to 500ml of 1.5wt.% 4-[2-(trimethoxysilyl)ethyl]benzene-1-sulfonyl azide compound dilute solution and mechanically stirred for 60min, then taken out, rinsed and dried to obtain the modified polymer expanded microspheres.
[0061] 14 g of brucite mineral fiber was added into 600 ml of 2 wt.% KH-792 dilute solution and ultrasonically dispersed for 2 h. The solution was taken out, rinsed, dried, ground and sieved to obtain the modified mineral fiber.
[0062] 6 g of hydrophobic SiO2 aerogel was added into 60 ml of 3 wt.% PVA dilute solution and mechanically stirred for 45 h. The solution was taken out, freeze-dried, crushed and sieved to obtain the PVA toughened and modified hydrophobic SiO2 aerogel.
[0063] 2) Preparation of thermal insulation protective coating:
[0064] 14 parts by mass of deionized water, 0.3 parts by mass of thickener, 0.25 parts by mass of pH regulator, 4 parts by mass of dispersant, 1.8 parts by mass of defoamer, 14 parts by mass of modified mineral fiber and 6 parts by mass of PVA toughened modified hydrophobic SiO2 aerogel are placed in a container and dispersed and mixed evenly at high speed. Then the speed is reduced and 14 parts by mass of silicone resin emulsion, 18 parts by mass of acetic acid propylene emulsion, 1.8 parts by mass of ethylene glycol, 6 parts by mass of film-forming aid, 16 parts by mass of modified polymer expanded microspheres, 3 parts by mass of cross-linking agent ethyltrimethoxysilane and 0.4 parts by mass of catalyst hexachlorocyclotriphosphazene are added in sequence and mechanical stirring is continued for 30 minutes to obtain a mixed coating.
[0065] The mixed coating was then scraped onto the surface of the surface treated concrete substrate with a thickness of 1 mm and cured and dried under standard conditions to obtain a self-resilient thermal insulation protective coating with ultra-low thermal conductivity.
[0066] Example 4
[0067] 1) Preparation of modified polymer expanded microspheres, modified mineral fibers and PVA toughened modified hydrophobic SiO2 aerogels:
[0068] Take 170g Expancel 921WE 40( Solid content 10% polymer expanded microspheres (pure microsphere mass 17g) were added into 600ml of 2wt.% KH-591 dilute solution and mechanically stirred for 60min, then taken out, rinsed and dried to obtain the modified polymer expanded microspheres.
[0069] 15 g of sepiolite mineral fiber was added into 800 ml of 2 wt.% KH-570 dilute solution and ultrasonically dispersed for 2 h. The fiber was taken out, rinsed, dried, ground and sieved to obtain the modified mineral fiber.
[0070] 5 g of hydrophobic SiO2 aerogel was added into 50 ml of 3 wt.% PVA dilute solution and mechanically stirred for 48 h. The solution was taken out, freeze-dried, crushed and sieved to obtain the PVA toughened and modified hydrophobic SiO2 aerogel.
[0071] 2) Preparation of thermal insulation protective coating:
[0072] 13 parts by mass of deionized water, 0.2 parts by mass of thickener, 0.5 parts by mass of pH regulator, 4.5 parts by mass of dispersant, 2 parts by mass of defoamer, 15 parts by mass of modified mineral fiber and 5 parts by mass of PVA toughened modified hydrophobic SiO2 aerogel are placed in a container and dispersed and mixed evenly at high speed. Then the speed is reduced and 15 parts by mass of silicone resin emulsion, 20 parts by mass of pure acrylic emulsion, 1.6 parts by mass of ethylene glycol, 7.5 parts by mass of film-forming aid, 17 parts by mass of modified polymer expanded microspheres, 5 parts by mass of cross-linking agent methylphenyldiethoxysilane and 0.2 parts by mass of catalyst dibutyltin dilaurate are added in sequence and mechanical stirring is continued for 30 minutes to obtain a mixed coating.
[0073] The mixed coating was then scraped onto the surface of the surface treated concrete substrate with a thickness of 1 mm and cured and dried under standard conditions to obtain a self-resilient thermal insulation protective coating with ultra-low thermal conductivity.
[0074] Example 5
[0075] 1) Preparation of modified polymer expanded microspheres, modified mineral fibers and PVA toughened modified hydrophobic SiO2 aerogels:
[0076] Take 133.33g MH-30W15( Solid content 15% polymer expanded microspheres (pure microsphere mass 20g) were added into 700ml of 1.8wt.% KH-591 dilute solution and mechanically stirred for 50min, then taken out, rinsed and dried to obtain the modified polymer expanded microspheres.
[0077] 11 g of aluminum silicate mineral fiber was added into 600 ml of 2 wt.% KH-580 dilute solution and ultrasonically dispersed for 1.5 h. The solution was taken out, rinsed, dried, ground and sieved to obtain the modified mineral fiber.
[0078] 5.5 g of hydrophobic SiO2 aerogel was added into 55 ml of 2.5 wt.% PVA dilute solution and mechanically stirred for 45 h. The solution was taken out, freeze-dried, crushed and sieved to obtain the PVA toughened and modified hydrophobic SiO2 aerogel.
[0079] 2) Preparation of thermal insulation protective coating:
[0080] 15 parts by mass of deionized water, 0.25 parts by mass of thickener, 0.1 parts by mass of pH adjuster, 5 parts by mass of dispersant, 2 parts by mass of defoamer, 11 parts by mass of modified mineral fiber and 5.5 parts by mass of PVA toughened modified hydrophobic SiO2 aerogel are placed in a container and dispersed and mixed evenly at high speed. Then the speed is reduced and 11 parts by mass of silicone resin emulsion, 21 parts by mass of silicone acrylic emulsion, 1.7 parts by mass of ethylene glycol, 6.5 parts by mass of film-forming aid, 20 parts by mass of modified polymer expanded microspheres, 2.5 parts by mass of cross-linking agent vinyl trisbutyl ketoxime silane and 0.8 parts by mass of catalyst tin cyclohexane are added in sequence and mechanical stirring is continued for 30 minutes to obtain a mixed coating.
[0081] The mixed coating was then scraped onto the surface of the surface treated concrete substrate with a thickness of 1 mm and cured and dried under standard conditions to obtain a self-resilient thermal insulation protective coating with ultra-low thermal conductivity.
[0082] Example 6
[0083] 1) Preparation of modified polymer expanded microspheres, modified mineral fibers and PVA toughened modified hydrophobic SiO2 aerogel:
[0084] Take 126.67g Expancel 044WE 20( Solid content 15% polymer expanded microspheres (pure microsphere mass 19g) were added into 600ml of 1wt.% dilute solution of (dimethylaminoethyl methacrylate)propyltrimethoxysilane chloride and mechanically stirred for 45min, then taken out, rinsed and dried to obtain the modified polymer expanded microspheres.
[0085] 11.5 g of sepiolite mineral fiber was added into 700 ml of 2 wt.% KH-550 dilute solution and ultrasonically dispersed for 1 hour. The solution was taken out, rinsed, dried, ground and sieved to obtain the modified mineral fiber.
[0086] 6 g of hydrophobic SiO2 aerogel was added into 50 ml of 3 wt.% PVA dilute solution and mechanically stirred for 38 h. The solution was taken out, freeze-dried, crushed and sieved to obtain the PVA toughened and modified hydrophobic SiO2 aerogel.
[0087] 2) Preparation of thermal insulation protective coating:
[0088] 14 parts by mass of deionized water, 0.15 parts by mass of thickener, 0.35 parts by mass of pH adjuster, 3.5 parts by mass of dispersant, 1 part by mass of defoamer, 11.5 parts by mass of modified mineral fiber and 6 parts by mass of PVA toughened modified hydrophobic SiO2 aerogel are placed in a container and dispersed and mixed evenly at high speed. Then the speed is reduced and 14 parts by mass of silicone resin emulsion, 17 parts by mass of styrene acrylic emulsion, 1.9 parts by mass of ethylene glycol, 8 parts by mass of film-forming aid, 19 parts by mass of modified polymer expanded microspheres, 2.5 parts by mass of cross-linking agent vinyl triethoxy silane and 0.6 parts by mass of catalyst stannous octoate are added in sequence and mechanical stirring is continued for 30 minutes to obtain a mixed coating.
[0089] The mixed coating was then scraped onto the surface of the surface treated concrete substrate with a thickness of 1 mm and cured and dried under standard conditions to obtain a self-resilient thermal insulation protective coating with ultra-low thermal conductivity.
[0090] Example 7
[0091] 1) Preparation of modified polymer expanded microspheres, modified mineral fibers and PVA toughened modified hydrophobic SiO2 aerogels:
[0092] Take 160g Expancel 921WE 40( Solid content 10%) polymer expanded microspheres (pure microsphere mass 16g) were added into 700ml of 1.6wt.% KH-591 dilute solution and mechanically stirred for 35min, then taken out, rinsed and dried to obtain the modified polymer expanded microspheres.
[0093] 13 g of sepiolite mineral fiber was added into 600 ml of 1.8 wt.% KH-892 dilute solution and ultrasonically dispersed for 1.5 h. The fiber was taken out, rinsed, dried, ground and sieved to obtain the modified mineral fiber.
[0094] 7 g of hydrophobic SiO2 aerogel was added into 70 ml of 2.5 wt.% PVA dilute solution and mechanically stirred for 45 h. The solution was taken out, freeze-dried, crushed and sieved to obtain the PVA toughened and modified hydrophobic SiO2 aerogel.
[0095] 2) Preparation of thermal insulation protective coating:
[0096] 15 parts by mass of deionized water, 0.2 parts by mass of thickener, 0.3 parts by mass of pH adjuster, 4.5 parts by mass of dispersant, 1.6 parts by mass of defoamer, 13 parts by mass of modified mineral fiber and 7 parts by mass of PVA toughened modified hydrophobic SiO2 aerogel are placed in a container and dispersed and mixed evenly at high speed. Then the speed is reduced and 10 parts by mass of silicone resin emulsion, 19 parts by mass of silicone acrylic emulsion, 2 parts by mass of ethylene glycol, 7 parts by mass of film-forming aid, 16 parts by mass of modified polymer expanded microspheres, 4.5 parts by mass of cross-linking agent polybutylene adipate and 0.5 parts by mass of catalyst hexachlorocyclotriphosphazene are added in sequence and mechanical stirring is continued for 30 minutes to obtain a mixed coating.
[0097] The mixed coating was then scraped onto the surface of the surface treated concrete substrate with a thickness of 1 mm and cured and dried under standard conditions to obtain a self-resilient thermal insulation protective coating with ultra-low thermal conductivity.
[0098] Example 8
[0099] 1) Preparation of modified polymer expanded microspheres, modified mineral fibers and PVA toughened modified hydrophobic SiO2 aerogels:
[0100] Take 120g MH-60W15( Solid content 15%) polymer expanded microspheres (pure microsphere mass 18g) were added to 900ml of 2wt.% 4-[2-(trimethoxysilyl)ethyl]benzene-1-sulfonyl azide compound dilute solution and mechanically stirred for 60min, then taken out, rinsed and dried to obtain the modified polymer expanded microspheres.
[0101] 12 g of brucite mineral fiber was added into 800 ml of 1.5 wt.% KH-550 dilute solution and ultrasonically dispersed for 1.5 h. The solution was taken out, rinsed, dried, ground and sieved to obtain the modified mineral fiber.
[0102] 6 g of hydrophobic SiO2 aerogel was added into 60 ml of 3 wt.% PVA dilute solution and mechanically stirred for 48 h. The solution was taken out, freeze-dried, crushed and sieved to obtain the PVA toughened and modified hydrophobic SiO2 aerogel.
[0103] 2) Preparation of thermal insulation protective coating:
[0104] 14 parts by mass of deionized water, 0.5 parts by mass of thickener, 0.5 parts by mass of pH regulator, 5 parts by mass of dispersant, 1.5 parts by mass of defoamer, 12 parts by mass of modified mineral fiber and 6 parts by mass of PVA toughened modified hydrophobic SiO2 aerogel are placed in a container and dispersed and mixed evenly at high speed. Then the speed is reduced and 13.5 parts by mass of silicone resin emulsion, 16 parts by mass of acetic acid propylene emulsion, 1.7 parts by mass of ethylene glycol, 5 parts by mass of film-forming aid, 18 parts by mass of modified polymer expanded microspheres, 3.5 parts by mass of cross-linking agent methyl tributylidene silane and 1 part by mass of catalyst tin cyclohexane are added in sequence and mechanical stirring is continued for 30 minutes to obtain a mixed coating.
[0105] The mixed coating was then scraped onto the surface of the surface treated concrete substrate with a thickness of 1 mm and cured and dried under standard conditions to obtain a self-resilient thermal insulation protective coating with ultra-low thermal conductivity.
[0106] Comparative Example 1
[0107] 1) Preparation of modified polymer expanded microspheres and modified mineral fibers:
[0108] Take 100g Expancel 044WE 20( Solid content 15% polymer expanded microspheres (pure microsphere mass 15g) were added into 1000ml of 2wt.% KH-591 dilute solution and mechanically stirred for 40min, then taken out, rinsed and dried to obtain the modified polymer expanded microspheres.
[0109] 12 g of sepiolite mineral fiber was added into 800 ml of 1.5 wt.% KH-550 dilute solution and ultrasonically dispersed for 2 h. The solution was taken out, rinsed, dried, ground and sieved to obtain the modified mineral fiber.
[0110] 2) Preparation of thermal insulation protective coating:
[0111] 15 parts by mass of deionized water, 0.35 parts by mass of thickener, 0.4 parts by mass of pH adjuster, 5 parts by mass of dispersant, 2 parts by mass of defoamer, 12 parts by mass of modified mineral fiber and 8 parts by mass of hydrophobic SiO2 aerogel are placed in a container and dispersed and mixed evenly at high speed. Then the speed is reduced and 13 parts by mass of silicone resin emulsion, 22 parts by mass of styrene acrylic emulsion, 1.5 parts by mass of ethylene glycol, 8 parts by mass of film-forming aid, 15 parts by mass of modified polymer expanded microspheres, 4 parts by mass of cross-linking agent polyethylene adipate and 0.1 parts by mass of catalyst dibutyltin dilaurate are added in sequence, and mechanical stirring is continued for 30 minutes to obtain a mixed coating.
[0112] The mixed coating was then scraped onto the surface of the surface treated concrete substrate with a thickness of 1 mm and cured and dried under standard conditions to obtain a self-resilient thermal insulation protective coating with ultra-low thermal conductivity.
[0113] Comparative Example 2
[0114] 1) Preparation of modified polymer expanded microspheres and PVA toughened modified hydrophobic SiO2 aerogel:
[0115] Take 100g Expancel 044WE 20( Solid content 15% polymer expanded microspheres (pure microsphere mass 15g) were added into 1000ml of 2wt.% KH-591 dilute solution and mechanically stirred for 40min, then taken out, rinsed and dried to obtain the modified polymer expanded microspheres.
[0116] 8 g of hydrophobic SiO2 aerogel was added into 100 ml of 2 wt.% PVA dilute solution and mechanically stirred for 48 h. The solution was taken out, freeze-dried, crushed and sieved to obtain the PVA toughened and modified hydrophobic SiO2 aerogel.
[0117] 2) Preparation of thermal insulation protective coating:
[0118] 15 parts by mass of deionized water, 0.35 parts by mass of thickener, 0.4 parts by mass of pH adjuster, 5 parts by mass of dispersant, 2 parts by mass of defoamer, 12 parts by mass of sepiolite mineral fiber and 8 parts by mass of PVA toughened modified hydrophobic SiO2 aerogel are placed in a container and dispersed and mixed evenly at high speed. Then the speed is reduced and 13 parts by mass of silicone resin emulsion, 22 parts by mass of styrene acrylic emulsion, 1.5 parts by mass of ethylene glycol, 8 parts by mass of film-forming aid, 15 parts by mass of modified polymer expanded microspheres, 4 parts by mass of cross-linking agent polyethylene adipate and 0.1 parts by mass of catalyst dibutyltin dilaurate are added in sequence and mechanical stirring is continued for 30 minutes to obtain a mixed coating.
[0119] The mixed coating was then scraped onto the surface of the surface treated concrete substrate with a thickness of 1 mm and cured and dried under standard conditions to obtain a self-resilient thermal insulation protective coating with ultra-low thermal conductivity.
[0120] Comparative Example 3
[0121] 1) Preparation of modified mineral fiber and PVA toughened modified hydrophobic SiO2 aerogel:
[0122] 12 g of sepiolite mineral fiber was added into 800 ml of 1.5 wt.% KH-550 dilute solution and ultrasonically dispersed for 2 h. The solution was taken out, rinsed, dried, ground and sieved to obtain the modified mineral fiber.
[0123] 8 g of hydrophobic SiO2 aerogel was added into 100 ml of 2 wt.% PVA dilute solution and mechanically stirred for 48 h. The solution was taken out, freeze-dried, crushed and sieved to obtain the PVA toughened and modified hydrophobic SiO2 aerogel.
[0124] 2) Preparation of thermal insulation protective coating:
[0125] 15 parts by weight of deionized water, 0.35 parts by weight of thickener, 0.4 parts by weight of pH regulator, 5 parts by weight of dispersant, 2 parts by weight of defoamer, 12 parts by weight of modified mineral fiber and 8 parts by weight of PVA toughened modified hydrophobic SiO2 aerogel were placed in a container and dispersed and mixed uniformly at high speed, then the speed was reduced and 13 parts by weight of silicone resin emulsion, 22 parts by weight of styrene acrylic emulsion, 1.5 parts by weight of ethylene glycol, 8 parts by weight of film-forming aid, and dried Expancel 044WE 20( 15 parts by weight of polymer expanded microspheres (solid content 15%), 4 parts by weight of crosslinking agent polyethylene adipate and 0.1 parts by weight of catalyst dibutyltin dilaurate were added and mechanical stirring was continued for 30 minutes to obtain a mixed coating.
[0126] The mixed coating was then scraped onto the surface of the surface treated concrete substrate with a thickness of 1 mm and cured and dried under standard conditions to obtain a self-resilient thermal insulation protective coating with ultra-low thermal conductivity.
[0127] Comparative Example 4
[0128] 1) Preparation of PVA toughened modified hydrophobic SiO2 aerogel:
[0129] 5 g of hydrophobic SiO2 aerogel was added into 50 ml of 2.5 wt.% PVA dilute solution at room temperature and mechanically stirred for 40 h. The solution was taken out, freeze-dried, crushed and sieved to obtain the PVA toughened and modified hydrophobic SiO2 aerogel.
[0130] 2) Preparation of thermal insulation protective coating:
[0131] 12 parts by mass of deionized water, 0.4 parts by mass of thickener, 0.3 parts by mass of pH regulator, 3 parts by mass of dispersant, 1.5 parts by mass of defoamer, 10 parts by mass of aluminum silicate mineral fiber and 5 parts by mass of PVA toughened modified hydrophobic SiO2 aerogel were placed in a container and dispersed and mixed uniformly at high speed, then the speed was reduced and 12.5 parts by mass of silicone resin emulsion, 25 parts by mass of silicone acrylic emulsion, 2 parts by mass of ethylene glycol, 7 parts by mass of film-forming aid, and MH-30W15( 18 parts by weight of polymer expanded microspheres (solid content 15%), 2 parts by weight of methyl tributylidene silane as a crosslinking agent and 0.5 parts by weight of stannous octoate as a catalyst were added and mechanical stirring was continued for 30 minutes to obtain a mixed coating.
[0132] The mixed coating was then scraped onto the surface of the surface treated concrete substrate with a thickness of 1 mm and cured and dried under standard conditions to obtain a self-resilient thermal insulation protective coating with ultra-low thermal conductivity.
[0133] Comparative Example 5
[0134] 1) Preparation of modified polymer expanded microspheres:
[0135] Take 120g MH-30W15( Solid content 15% polymer expanded microspheres (pure microsphere mass 18g) were added into 600ml of 1.8wt.% dilute solution of (dimethylaminoethyl methacrylate)propyltrimethoxysilane chloride and mechanically stirred for 50min, then taken out, rinsed and dried to obtain the modified polymer expanded microspheres.
[0136] 2) Preparation of thermal insulation protective coating:
[0137] 12 parts by mass of deionized water, 0.4 parts by mass of thickener, 0.3 parts by mass of pH adjuster, 3 parts by mass of dispersant, 1.5 parts by mass of defoamer, 10 parts by mass of aluminum silicate mineral fiber and 5 parts by mass of hydrophobic SiO2 aerogel are placed in a container and dispersed and mixed evenly at high speed. Then the speed is reduced and 12.5 parts by mass of silicone resin emulsion, 25 parts by mass of silicone acrylic emulsion, 2 parts by mass of ethylene glycol, 7 parts by mass of film-forming aid, 18 parts by mass of modified polymer expanded microspheres, 2 parts by mass of cross-linking agent methyl tributylidene silane and 0.5 parts by mass of catalyst stannous octoate are added in sequence and mechanical stirring is continued for 30 minutes to obtain a mixed coating.
[0138] The mixed coating was then scraped onto the surface of the surface treated concrete substrate with a thickness of 1 mm and cured and dried under standard conditions to obtain a self-resilient thermal insulation protective coating with ultra-low thermal conductivity.
[0139] Comparative Example 6
[0140] 1) Preparation of modified mineral fibers:
[0141] 10 g of aluminum silicate mineral fiber was added into 800 ml of 2 wt.% KH-188 dilute solution and ultrasonically dispersed for 1.5 h. The fiber was taken out, rinsed, dried, ground and sieved to obtain the modified mineral fiber.
[0142] 2) Preparation of thermal insulation protective coating:
[0143] 12 parts by mass of deionized water, 0.4 parts by mass of thickener, 0.3 parts by mass of pH regulator, 3 parts by mass of dispersant, 1.5 parts by mass of defoamer, 10 parts by mass of modified mineral fiber and 5 parts by mass of hydrophobic SiO2 aerogel were placed in a container and dispersed and mixed uniformly at high speed, then the speed was reduced and 12.5 parts by mass of silicone resin emulsion, 25 parts by mass of silicone acrylic emulsion, 2 parts by mass of ethylene glycol, 7 parts by mass of film-forming aid, and MH-30W15( 18 parts by weight of polymer expanded microspheres (solid content 15%), 2 parts by weight of methyl tributylidene silane as a crosslinking agent and 0.5 parts by weight of stannous octoate as a catalyst were added and mechanical stirring was continued for 30 minutes to obtain a mixed coating.
[0144] The mixed coating was then scraped onto the surface of the surface treated concrete substrate with a thickness of 1 mm and cured and dried under standard conditions to obtain a self-resilient thermal insulation protective coating with ultra-low thermal conductivity.
[0145] Comparative Example 7
[0146] 1) Preparation of thermal insulation protective coating:
[0147] 14 parts by mass of deionized water, 0.3 parts by mass of thickener, 0.25 parts by mass of pH regulator, 4 parts by mass of dispersant, 1.8 parts by mass of defoamer, 14 parts by mass of brucite mineral fiber and 6 parts by mass of hydrophobic SiO2 aerogel were placed in a container and dispersed and mixed uniformly at high speed, and then the speed was reduced and 14 parts by mass of silicone resin emulsion, 18 parts by mass of acetic acid propylene emulsion, 1.8 parts by mass of ethylene glycol, 6 parts by mass of film-forming aid, and MH-60W15( 16 parts by weight of polymer expanded microspheres (solid content 15%), 3 parts by weight of crosslinking agent ethyltrimethoxysilane and 0.4 parts by weight of catalyst hexachlorocyclotriphosphazene were added and mechanical stirring was continued for 30 minutes to obtain a mixed coating.
[0148] The mixed coating was then scraped onto the surface of the surface treated concrete substrate with a thickness of 1 mm and cured and dried under standard conditions to obtain a self-resilient thermal insulation protective coating with ultra-low thermal conductivity.
[0149] Comparative Example 8
[0150] 1) Preparation of modified polymer expanded microspheres, modified mineral fibers and PVA toughened modified hydrophobic SiO2 aerogel:
[0151] Take 170g Expancel 921WE 40( Solid content 10% polymer expanded microspheres (pure microsphere mass 17g) were added into 600ml of 2wt.% KH-591 dilute solution and mechanically stirred for 60min, then taken out, rinsed and dried to obtain the modified polymer expanded microspheres.
[0152] 15 g of sepiolite mineral fiber was added into 800 ml of 2 wt.% KH-570 dilute solution and ultrasonically dispersed for 2 h. The fiber was taken out, rinsed, dried, ground and sieved to obtain the modified mineral fiber.
[0153] 5 g of hydrophobic SiO2 aerogel was added into 50 ml of 3 wt.% PVA dilute solution and mechanically stirred for 48 h. The solution was taken out, freeze-dried, crushed and sieved to obtain the PVA toughened and modified hydrophobic SiO2 aerogel.
[0154] 2) Preparation of thermal insulation protective coating:
[0155] 13 parts by mass of deionized water, 0.2 parts by mass of thickener, 0.5 parts by mass of pH regulator, 4.5 parts by mass of dispersant, 2 parts by mass of defoamer, 15 parts by mass of modified mineral fiber and 5 parts by mass of PVA toughened modified hydrophobic SiO2 aerogel are placed in a container and dispersed and mixed evenly at high speed. Then the speed is reduced and 35 parts by mass of silicone resin emulsion (containing only silicone resin emulsion), 1.6 parts by mass of ethylene glycol, 7.5 parts by mass of film-forming aid, 17 parts by mass of modified polymer expanded microspheres, 5 parts by mass of cross-linking agent methylphenyldiethoxysilane and 0.2 parts by mass of catalyst dibutyltin dilaurate are added in sequence and mechanical stirring is continued for 30 minutes to obtain a mixed coating.
[0156] The mixed coating was then scraped onto the surface of the surface treated concrete substrate with a thickness of 1 mm and cured and dried under standard conditions to obtain a self-resilient thermal insulation protective coating with ultra-low thermal conductivity.
[0157] Comparative Example 9
[0158] 1) Preparation of modified polymer expanded microspheres, modified mineral fibers and PVA toughened modified hydrophobic SiO2 aerogel:
[0159] Take 170g Expancel 921WE 40( Solid content 10% polymer expanded microspheres (pure microsphere mass 17g) were added into 600ml of 2wt.% KH-591 dilute solution and mechanically stirred for 60min, then taken out, rinsed and dried to obtain the modified polymer expanded microspheres.
[0160] 15 g of sepiolite mineral fiber was added into 800 ml of 2 wt.% KH-570 dilute solution and ultrasonically dispersed for 2 h. The fiber was taken out, rinsed, dried, ground and sieved to obtain the modified mineral fiber.
[0161] 5 g of hydrophobic SiO2 aerogel was added into 50 ml of 3 wt.% PVA dilute solution and mechanically stirred for 48 h. The solution was taken out, freeze-dried, crushed and sieved to obtain the PVA toughened and modified hydrophobic SiO2 aerogel.
[0162] 2) Preparation of thermal insulation protective coating:
[0163] 13 parts by mass of deionized water, 0.2 parts by mass of thickener, 0.5 parts by mass of pH regulator, 4.5 parts by mass of dispersant, 2 parts by mass of defoamer, 15 parts by mass of modified mineral fiber and 5 parts by mass of PVA toughened modified hydrophobic SiO2 aerogel are placed in a container and dispersed and mixed evenly at high speed. Then the speed is reduced and 15 parts by mass of hydroxyl-terminated polydimethylsiloxane emulsion, 20 parts by mass of pure acrylic emulsion, 1.6 parts by mass of ethylene glycol, 7.5 parts by mass of film-forming aid, 17 parts by mass of modified polymer expanded microspheres, 5 parts by mass of cross-linking agent methylphenyldiethoxysilane and 0.2 parts by mass of catalyst dibutyltin dilaurate are added in sequence, and mechanical stirring is continued for 30 minutes to obtain a mixed coating.
[0164] The mixed coating was then scraped onto the surface of the surface treated concrete substrate with a thickness of 1 mm and cured and dried under standard conditions to obtain a self-resilient thermal insulation protective coating with ultra-low thermal conductivity.
[0165] Comparative Example 10
[0166] 1) Preparation of modified polymer expanded microspheres, modified mineral fibers and PVA toughened modified hydrophobic SiO2 aerogel:
[0167] Take 170g Expancel 921WE 40( Solid content 10% polymer expanded microspheres (pure microsphere mass 17g) were added into 600ml of 2wt.% KH-591 dilute solution and mechanically stirred for 60min, then taken out, rinsed and dried to obtain the modified polymer expanded microspheres.
[0168] 15 g of sepiolite mineral fiber was added into 800 ml of 2 wt.% KH-570 dilute solution and ultrasonically dispersed for 2 h. The fiber was taken out, rinsed, dried, ground and sieved to obtain the modified mineral fiber.
[0169] 5 g of hydrophobic SiO2 aerogel was added into 50 ml of 3 wt.% PVA dilute solution and mechanically stirred for 48 h. The solution was taken out, freeze-dried, crushed and sieved to obtain the PVA toughened and modified hydrophobic SiO2 aerogel.
[0170] 2) Preparation of thermal insulation protective coating:
[0171] 13 parts by mass of deionized water, 0.2 parts by mass of thickener, 0.5 parts by mass of pH regulator, 4.5 parts by mass of dispersant, 2 parts by mass of defoamer, 15 parts by mass of modified mineral fiber and 5 parts by mass of PVA toughened modified hydrophobic SiO2 aerogel are placed in a container and dispersed and mixed evenly at high speed. Then the speed is reduced and 35 parts by mass of pure acrylic emulsion (containing only acrylic resin emulsion), 1.6 parts by mass of ethylene glycol, 7.5 parts by mass of film-forming aid, 17 parts by mass of modified polymer expanded microspheres, 5 parts by mass of cross-linking agent methylphenyldiethoxysilane and 0.2 parts by mass of catalyst dibutyltin dilaurate are added in sequence and mechanical stirring is continued for 30 minutes to obtain a mixed coating.
[0172] The mixed coating was then scraped onto the surface of the surface treated concrete substrate with a thickness of 1 mm and cured and dried under standard conditions to obtain a self-resilient thermal insulation protective coating with ultra-low thermal conductivity.
[0173] Comparative Example 11
[0174] 1) Preparation of modified hollow glass microspheres, modified mineral fibers and PVA toughened modified hydrophobic SiO2 aerogels:
[0175] Take 18g of commercially available K1 ( Hollow glass microspheres with a solid content of 100% (solid content 100%) were added to 900 ml of a 2wt.% dilute solution of 4-[2-(trimethoxysilyl)ethyl]benzene-1-sulfonyl azide compound and mechanically stirred for 60 minutes. The modified hollow glass microspheres were taken out, rinsed and dried to obtain the modified hollow glass microspheres.
[0176] 12 g of brucite mineral fiber was added into 800 ml of 1.5 wt.% KH-550 dilute solution and ultrasonically dispersed for 1.5 h. The solution was taken out, rinsed, dried, ground and sieved to obtain the modified mineral fiber.
[0177] 6 g of hydrophobic SiO2 aerogel was added into 60 ml of 3 wt.% PVA dilute solution and mechanically stirred for 48 h. The solution was taken out, freeze-dried, crushed and sieved to obtain the PVA toughened and modified hydrophobic SiO2 aerogel.
[0178] 2) Preparation of thermal insulation protective coating:
[0179] 14 parts by mass of deionized water, 0.5 parts by mass of thickener, 0.5 parts by mass of pH adjuster, 5 parts by mass of dispersant, 1.5 parts by mass of defoamer, 12 parts by mass of modified mineral fiber and 6 parts by mass of PVA toughened modified hydrophobic SiO2 aerogel are placed in a container and dispersed and mixed evenly at high speed. Then the speed is reduced and 13.5 parts by mass of silicone resin emulsion, 16 parts by mass of acetic acid propylene emulsion, 1.7 parts by mass of ethylene glycol, 5 parts by mass of film-forming aid, 18 parts by mass of modified hollow glass microspheres, 3.5 parts by mass of cross-linking agent methyl tributylidene silane and 1 part by mass of catalyst tin cyclohexane are added in sequence and mechanical stirring is continued for 30 minutes to obtain a mixed coating.
[0180] The mixed coating was then scraped onto the surface of the surface treated concrete substrate with a thickness of 1 mm and cured and dried under standard conditions to obtain a self-resilient thermal insulation protective coating with ultra-low thermal conductivity.
[0181] Comparative Example 12
[0182] 1) Preparation of modified polymer expanded microspheres, modified mineral fibers and PVA toughened modified hydrophobic SiO2 aerogels:
[0183] Take 26.76g of commercially available 551WU 40 ( The polymer microspheres (solid content 71%) (pure microsphere mass 19g) were added into 600ml of 1wt.% dilute solution of (dimethylaminoethyl methacrylate)propyltrimethoxysilane chloride and mechanically stirred for 45min, then taken out, rinsed and dried to obtain the modified polymer microspheres.
[0184] 11.5 g of sepiolite mineral fiber was added into 700 ml of 2 wt.% KH-550 dilute solution and ultrasonically dispersed for 1 hour. The solution was taken out, rinsed, dried, ground and sieved to obtain the modified mineral fiber.
[0185] 6 g of hydrophobic SiO2 aerogel was added into 50 ml of 3 wt.% PVA dilute solution and mechanically stirred for 38 h. The solution was taken out, freeze-dried, crushed and sieved to obtain the PVA toughened and modified hydrophobic SiO2 aerogel.
[0186] 2) Preparation of thermal insulation protective coating:
[0187] 14 parts by mass of deionized water, 0.15 parts by mass of thickener, 0.35 parts by mass of pH adjuster, 3.5 parts by mass of dispersant, 1 part by mass of defoamer, 11.5 parts by mass of modified mineral fiber and 6 parts by mass of PVA toughened modified hydrophobic SiO2 aerogel are placed in a container and dispersed and mixed evenly at high speed. Then the speed is reduced and 14 parts by mass of silicone resin emulsion, 17 parts by mass of styrene acrylic emulsion, 1.9 parts by mass of ethylene glycol, 8 parts by mass of film-forming aid, 19 parts by mass of modified polymer microspheres, 2.5 parts by mass of cross-linking agent vinyl triethoxy silane and 0.6 parts by mass of catalyst stannous octoate are added in sequence and mechanical stirring is continued for 30 minutes to obtain a mixed coating.
[0188] The mixed coating was then scraped onto the surface of the surface treated concrete substrate with a thickness of 1 mm and cured and dried under standard conditions to obtain a self-resilient thermal insulation protective coating with ultra-low thermal conductivity.
[0189] Comparative Example 13
[0190] 1) Preparation of modified polymer expanded microspheres, modified mineral fibers and PVA toughened modified hydrophobic SiO2 aerogel:
[0191] Take 126.67g of commercially available MH-80W15 ( Solid content 15% polymer expanded microspheres (pure microsphere mass 19g) were added into 600ml of 1wt.% dilute solution of (dimethylaminoethyl methacrylate)propyltrimethoxysilane chloride and mechanically stirred for 45min, then taken out, rinsed and dried to obtain the modified polymer expanded microspheres.
[0192] 11.5 g of sepiolite mineral fiber was added into 700 ml of 2 wt.% KH-550 dilute solution and ultrasonically dispersed for 1 hour. The solution was taken out, rinsed, dried, ground and sieved to obtain the modified mineral fiber.
[0193] 6 g of hydrophobic SiO2 aerogel was added into 50 ml of 3 wt.% PVA dilute solution and mechanically stirred for 38 h. The solution was taken out, freeze-dried, crushed and sieved to obtain the PVA toughened and modified hydrophobic SiO2 aerogel.
[0194] 2) Preparation of thermal insulation protective coating:
[0195] 14 parts by mass of deionized water, 0.15 parts by mass of thickener, 0.35 parts by mass of pH adjuster, 3.5 parts by mass of dispersant, 1 part by mass of defoamer, 11.5 parts by mass of modified mineral fiber and 6 parts by mass of PVA toughened modified hydrophobic SiO2 aerogel are placed in a container and dispersed and mixed evenly at high speed. Then the speed is reduced and 14 parts by mass of silicone resin emulsion, 17 parts by mass of styrene acrylic emulsion, 1.9 parts by mass of ethylene glycol, 8 parts by mass of film-forming aid, 19 parts by mass of modified polymer expanded microspheres, 2.5 parts by mass of cross-linking agent vinyl triethoxy silane and 0.6 parts by mass of catalyst stannous octoate are added in sequence and mechanical stirring is continued for 30 minutes to obtain a mixed coating.
[0196] The mixed coating was then scraped onto the surface of the surface treated concrete substrate with a thickness of 1 mm and cured and dried under standard conditions to obtain a self-resilient thermal insulation protective coating with ultra-low thermal conductivity.
[0197] Test Example 1: Basic performance of thermal insulation protective coating
[0198] According to "6.3.3 Preparation of Thermal Insulation Midcoat Test Pieces" in GB / T 25261-2018 "Reflective Thermal Insulation Coatings for Buildings", test pieces for testing the basic properties of thermal insulation protective coatings (low temperature stability, workability, film appearance, water resistance, alkali resistance, coating temperature change resistance, bonding strength, tensile strength, elongation at break and low temperature flexibility) were prepared. The performance test methods were carried out in accordance with "6.4 Operation Methods". The basic performance test results of each embodiment and comparative example are shown in Table 1 below:
[0199] Table 1
[0200]
[0201]
[0202] Test Example 2: Thermal insulation and protective coating functionality
[0203] Preparation process of thermal conductivity test sample of thermal insulation protective coating: Stir the coating in a container to mix well, pour it into a steel or plastic coating mold, use 2-3 molding processes, each with an interval of 24 hours, the test specimen size is 30cm×30cm×(1-2)cm, and after molding, cure it under standard conditions for 7 days. After removing the film, turn the reverse side upward and continue to cure under standard conditions for 7 days. Then test it at 25℃ according to GB / T 10294-2008 "Determination of Steady-State Thermal Resistance and Related Properties of Insulating Materials - Protective Hot Plate Method" test standard.
[0204] The preparation process of the thermal insulation temperature difference test sample of the thermal insulation protective coating adopts the preparation method of the coating in the embodiment and the comparative example. The test plate is C40 concrete, the test plate size is 100mm×100mm×6mm, the coating thickness is 1mm, and 3 coated test plates and blank test plates are prepared in parallel in each group. After the test plate is prepared, it is cured under standard conditions for 7 days. The thermal insulation temperature difference is tested by irradiation with an 80℃ non-contact infrared heating lamp: first, the sensors in the multi-channel temperature tester are respectively attached to the front and back of the test plate, and 9 are evenly attached to each side; then, the front of the coated test plate and the blank test plate are continuously and evenly irradiated with an infrared heating lamp for 15 minutes, and the average temperature of the front and back of the two groups of test plates is recorded by the multi-channel temperature tester, so as to calculate the thermal insulation temperature difference of the thermal insulation protective coating. The thermal insulation temperature difference was tested using an 80°C contact heating platform: the coated test panel and the blank test panel were placed face down close to the heating plate, and then the heating platform was used to uniformly heat the two groups of test panels at 80°C for 15 minutes. An infrared thermal imager was then used to measure the average temperature of the back of the two groups of test panels, thereby calculating the thermal insulation temperature difference of the thermal insulation protective coating.
[0205] The functional test results of each embodiment and comparative example are shown in Table 2 below:
[0206] Table 2
[0207]
[0208]
[0209] According to the test results of test examples 1 and 2, the thermal insulation protective coatings prepared in Examples 1-8 have good film-forming properties, are not easy to crack after curing and drying, and are not easy to crack after temperature change resistance testing, and have excellent corrosion resistance and mechanical properties, far exceeding the test standard requirements. Its thermal conductivity is between 0.018-0.020W / (m·k) at 25°C, and the thermal insulation temperature difference after 15 minutes of 80°C non-contact infrared heating lamp irradiation and 15 minutes of 80°C contact heating platform heating is greater than 35°C and 40°C, respectively, which is far more than the conventional commercially available aerogel thermal insulation protective coatings.
[0210] In Comparative Example 1, since the hydrophobic SiO2 aerogel added was not toughened and modified by PVA, it was easy to collapse in the coating and had poor compatibility. Therefore, the appearance of the paint film after curing collapsed and microcracks appeared in the coating after three temperature resistance tests; its thermal conductivity also increased significantly, and its thermal insulation performance decreased.
[0211] Comparative Examples 2-4 respectively represent mineral fibers that have not been modified with silane coupling agent I, polymer expanded microspheres that have not been modified with silane coupling agent II, and neither of them has been modified with silane coupling agent. Under the three conditions, the interface bonding between the filler and the film-forming substance in the coating is only physical bonding. After the coating is cured, the overall cross-linking crystallinity is not as good as that of Examples 1 and 2. In particular, the polymer expanded microspheres that occupy the largest volume ratio in the coating have not been modified with silane coupling agent II, and the cross-linking crystallinity is even lower after the coating is cured. Therefore, after three temperature change resistance tests under the three conditions, the coatings show a certain degree of microcracks, and the cracking phenomenon will be further aggravated by the influence of the external corrosive environment; the overall strength of the coating is reduced, and thus the mechanical properties such as bonding strength and tensile strength are reduced to a certain extent. After the bonding strength test of Comparative Examples 3 and 4, cohesive failure of the paint film occurs; the thermal insulation properties of the other three are also reduced to a certain extent.
[0212] In Comparative Examples 5-6, since the hydrophobic SiO2 aerogel was not toughened and modified by PVA, the coating collapsed to a certain extent after the paint film was cured. In addition, the polymer expanded microspheres in Comparative Example 6 were not modified by silane coupling agent II, which resulted in the coating's corrosion resistance, temperature change resistance, bonding strength, mechanical properties, low-temperature flexibility and other basic properties being reduced to an unfavorable degree. The thermal insulation effect of the coating was significantly reduced compared to Example 2.
[0213] The fillers (expanded polymer microspheres, mineral fibers and hydrophobic SiO2 aerogel) in Comparative Example 7 were not modified, and the paint film was prone to slight collapse and cracking after curing, and the uniformity was poor. Therefore, its corrosion resistance, temperature change resistance, bonding strength, mechanical properties and functionality were significantly reduced.
[0214] In Comparative Example 8, since the film-forming materials are all silicone resin emulsions, the cross-linking agent content is lower than that in Example 4. On the other hand, the silicone resin emulsion content is higher, and a higher temperature is required for heating and curing in a short time. Therefore, the performance of Comparative Example 4 is reduced to the minimum, and it basically has no thermal insulation properties.
[0215] In Comparative Example 9, conventional hydroxyl-terminated polydimethylsiloxane emulsion is used to replace hydroxyl-terminated polymethylphenylsiloxane emulsion, and its basic performance and functionality are not much different, but it cannot be ignored that the presence of phenyl in the silicone resin emulsion of the present invention can further improve the bonding strength and self-strength between the thermal insulation protective coating and the concrete substrate or primer. Therefore, by comparing Example 4 with Comparative Example 9, it is found that its bonding strength and tensile strength are increased by 13.2% and 15.2% respectively.
[0216] In Comparative Example 10, the film-forming material is all pure acrylic emulsion, and the low-temperature flexibility is poor. In addition, the curing and cross-linking process only relies on a small amount of cross-linking agent and silane coupling agent to solidify and cross-link, and the linear polymer chains of acrylic ester in the emulsion are lightly cross-linked into a network, and its cross-linking crystallinity is significantly reduced compared with Example 4, so its bonding strength, tensile properties and thermal insulation properties are reduced to a certain extent.
[0217] In Comparative Example 11, the polymer expanded microspheres are replaced with conventional hollow glass microspheres of the same particle size. First, the glass microspheres are brittle and fragile, and the coating can be easily broken by mechanical stirring during the preparation process, thereby losing part of the thermal insulation effect. On the other hand, compared with the polymer expanded microspheres, the glass microspheres do not have resilience, so the thermal insulation coating obtained is prone to irreparable dents under the action of external forces (as shown in the schematic diagram). In addition, the glass microspheres themselves have low strength, which reduces the strength of the thermal insulation coating itself in actual applications, so the bonding performance and tensile performance are much different from those of Example 8.
[0218] The particle size of the expanded polymer microspheres used in Comparative Examples 12-13 exceeds the specified range. When the particle size of the microspheres is small, the self-rebound effect of the corresponding thermal insulation coating is poor; and when the particle size of the microspheres is large, the corresponding thermal insulation coating has low self-strength. This results in a significant decrease in the tensile strength and elongation at break of the corresponding coating in Comparative Example 13 compared with Example 6. In addition, its low-temperature flexibility does not meet the standard, and a certain degree of microcracks appear.
[0219] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. An ultra-low thermal conductivity self-rebound thermal insulation protective coating, characterized in that: Calculated by weight, it includes 10-15 parts of silicone resin emulsion, 15-25 parts of acrylic resin emulsion, 15-20 parts of modified polymer expanded microspheres, 10-15 parts of modified mineral fibers, 5-8 parts of polyvinyl alcohol toughened modified hydrophobic silica aerogel, 1-5 parts of crosslinking agent, 0.1-1 parts of catalyst, 0.1-0.5 parts of thickener, 3-5 parts of dispersant, 1-2 parts of defoaming agent, 5-8 parts of film-forming aid, 0.1-0.5 parts of pH regulator, 1.5-2 parts of ethylene glycol and 10-15 parts of deionized water.
2. The ultra-low thermal conductivity self-resilient thermal insulation protective coating according to claim 1, characterized in that: The modified polymer expanded microspheres are polymer expanded microspheres surface-modified with silane coupling agent I, the polymer expanded microspheres are thermoplastic acrylate polymer / thermoplastic acrylonitrile copolymer shells coated with alkane or alkyne gas after heating and expansion, and the particle size of the polymer expanded microspheres ranges from 20 to 60 μm; the polymer expanded microspheres are selected from Expancel 044WE 20 ( Solid content 15%), Expancel 921WE 40 ( Solid content 10%), MH-30W15 ( Solid content 15%), MH-60W15 ( The invention relates to a method for preparing the present invention. The invention relates to a method for preparing the present invention. The invention relates to a method for preparing the present invention. The invention relates to a method for preparing the present invention. The invention relates to a method for preparing the present invention. The invention relates to a method for preparing the present invention. The invention relates to a method for preparing the present invention. The invention relates to a method for preparing the present invention. The invention relates to a method for preparing the present invention. The invention relates to a method for preparing the present invention. The invention relates to a method for preparing the present invention. The invention relates to a method for preparing the present invention. The invention relates to a method for preparing the present invention. The invention relates to a method for preparing the present invention.
3. The ultra-low thermal conductivity self-resilient thermal insulation protective coating according to claim 1, characterized in that: The modified mineral fiber is a mineral fiber surface-modified with a silane coupling agent II; the mineral fiber is a composite of any one or more of sepiolite fiber, aluminum silicate fiber, and brucite fiber, and the particle size of the mineral fiber is 1-3 mm; the silane coupling agent II is selected from vinyl trimethoxy silane, vinyl triethoxy silane, vinyl triacetoxy silane, vinyl-tri (2-methoxyethoxy) silane, γ-aminopropyl triethoxy silane, 3- (phenylamino) propyl trimethoxy silane, N-β- (aminoethyl) -γ -aminopropyltrimethoxysilane, 3-[2-(2-aminoethylamino)ethylamino]propyltrimethoxysilane, 3-chloropropyltrimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, γ-mercaptopropyltrimethoxysilane, γ-mercaptopropyltriethoxysilane, γ-aminopropylmethyldiethoxysilane or any one or more thereof; the concentration of the silane coupling agent II is 1-2wt.%; the mass volume ratio of the mineral fiber to the silane coupling agent is preferably (0.5-2)g:100ml.
4. The ultra-low thermal conductivity self-resilient thermal insulation protective coating according to claim 1, characterized in that: The polyvinyl alcohol used in the polyvinyl alcohol toughened modified hydrophobic silica aerogel has an average molecular weight of 70000-85000, a viscosity of 20-32 mPa·s, and a concentration of 1-3wt.%. The polyvinyl alcohol is selected from any one or more of commercially available 1788, 1792, 1795, 1796, 1797, and 1798; the mass ratio of the polyvinyl alcohol to the hydrophobic silica aerogel is preferably 10:(0.8-1.2).
5. The ultra-low thermal conductivity self-resilient thermal insulation protective coating according to claim 1, characterized in that: The silicone resin emulsion is a hydroxyl-terminated polymethylphenylsiloxane emulsion, and its organic solvent and emulsifier content is less than 10%; the acrylic resin emulsion is selected from any one or more of pure acrylic emulsion, styrene acrylic emulsion, silicone acrylic emulsion, and vinegar acrylic emulsion, and the solid content of the acrylic resin emulsion is 45%-55%.
6. The ultra-low thermal conductivity self-resilient thermal insulation protective coating according to claim 1, characterized in that: The crosslinking agent is any one of polyol esters, polyalkoxysilanes, and organic ketoxime silanes.
7. The ultra-low thermal conductivity self-resilient thermal insulation protective coating according to claim 1, characterized in that: The catalyst is a combination of any one or more of tin cyclohexaneate, dibutyltin dilaurate, stannous octoate and hexachlorocyclotriphosphazene.
8. The ultra-low thermal conductivity self-resilient thermal insulation protective coating according to claim 1, characterized in that: The thickener is selected from any one of hydroxyethyl cellulose and polyurethane associative thickener; the dispersant is selected from any one or more of polycarboxylate ammonium salt dispersants, alkylhydroxy ammonium salt dispersants, and non-ionic modified fatty acid derivative dispersants; the defoamer is selected from any one or more of polyether silicone defoamers, polysiloxane defoamers, metal soap defoamers, and paraffin defoamers; the film-forming aid is selected from any one or more of alcohol ester dodecahydrate, propylene glycol butyl ether, and dipropylene glycol butyl ether; and the pH adjuster is 2-amino-2-methyl-1-propanol.
9. The method for preparing the ultra-low thermal conductivity self-resilient thermal insulation protective coating according to claim 1, characterized in that: The method comprises the following steps: (1) placing deionized water, a thickener, a pH regulator, a dispersant, a defoaming agent, a modified mineral fiber and a polyvinyl alcohol toughened modified hydrophobic silica aerogel in a container, and dispersing and mixing them uniformly at a speed of 800-1000 rpm at room temperature, then reducing the speed to 400-500 rpm, adding silicone resin emulsion, acrylic resin emulsion, ethylene glycol, a film-forming aid, modified polymer expanded microspheres, a cross-linking agent, a catalyst and part of deionized water in sequence, and continuing mechanical stirring for 30 minutes, thereby obtaining an ultra-low thermal conductivity self-resilient thermal insulation protective coating.
10. A protective coating, formed by curing an ultra-low thermal conductivity self-resilient thermal insulation protective coating, characterized in that: The ultra-low thermal conductivity self-resilient thermal insulation protective coating is the ultra-low thermal conductivity self-resilient thermal insulation protective coating according to any one of claims 1 to 8.
Citation Information
Patent Citations
Preparation of novel environment-friendly aerogel heat insulation coating
CN115197619A
Nanometer high temperature resistant thermal insulation and prevention coating
CN104231917A
Micro-elastomer sound insulation coating and preparation method thereof
CN111040597A
Double-self-repairing outer heat-proof coating
CN113308183A
Silica aerogel reinforced polyvinyl alcohol composite material and preparation method thereof
CN115322502A
Cited By
Anti-collision rebounding colorful stone-like coating and preparation method thereof
CN120158219A